A Korean case of CTCF related neurodevelopmental disorders - Kang, Seong Ryeong; Seo, Soo Hyun; Kim, Kyunghoon; Yang, Hee Bum; Yang, Hye Ran; Cho, Anna (Journal of genetic medicine, 2023)
CCCTC-binding factor (CTCF) is a transcriptional regulator that binds to a complex DNA motif in various orientations and plays a crucial role in regulating gene expression, chromatin restructuring, and developmental processes. Mutations in the CTCF are associated with neurodevelopmental disorders. Here we report the first Korean case with a de novo heterozygous variant in the CTCF (c.1025G>A; p.Arg342His). She showed global developmental delay, failure to thrive, and dysmorphic face, which are phenotypes consistent with previous reports in the autosomal dominant intellectual developmental disorder 21 (MIM 615502). She also showed clinical features not previously reported, such as antral web and tracheobronchomalacia. Our case follows suit and expands understanding of this rare disorder by reporting common features and, on the other hand, unreported concomitant congenital anomalies. KCI Citation Count: 0